Identification and assessment of nutritive value of widely used feedstuffs for dairy cattle during yala season in vavuniya and mullaitivu districts of northern province, sri lanka - Thelaksan, T.; Mahipala, M.B.P.K.; Weerasinghe, W.M.P.B. (University of Jaffna, 2018)
Major roughage and concentrate feedstuffs used for dairy cattle feeding during Yala season in Vavuniya and Mullaitivu districts were investigated. A survey was conducted in 50, medium-scale cattle farms to identify the most widely used roughage and concentrate feedstuffs. Identified feedstuff samples collected from randomly selected farms were analyzed for dry matter (DM), ash and crude protein (CP) contents. They were further assessed for organic matter digestibility (OMD) and metabolizable energy (ME) content through in vitro gas fermentation assay. Most of the stall-fed farms largely fed the cattle with hybrid fodder sorghum (Sugargraze) and CO-3. Gliricidia, ipil-ipil and azolla are included to improve the quality of ration while straw and guinea grass are included to overcome feed shortage during Yala season. Grazing cattle largely depend on naturally grown, low quality guinea grass. More available rice polish, dhal dust, wheat bran and coconut meal are included in the cattle rations of many farms while less available black gram husk, gingelly meal and maize are included in rations of fewer farms. Nutritive value of roughage and concentrate feedstuffs for dairy cattle feeding varies (P<0.05). Guinea grass, CO-3 and Sugargraze are the potentially more digestible (OMD), energy (ME) rich roughages while Sugargraze would be the best option for dairy cattle feeding in Yala season. However, they should be harvested at proper maturity stage. Gliricidia, ipil-ipli and azolla can be recommended as protein (CP) supplementing forages. Coconut meal, black gram husk and gingelly meal could be recommended as energy (ME) and protein (CP) supplementing concentrates whilst maize could be recommended as the major energy (ME) supplement of the rations. Present study suggest to increase the availability of black gram husk, gingelly meal and maize for dairy cattle feeding and avoid adulteration of rice polish in order to prosper dairy cattle farming in Vavuniya and Mullaitivu districts.
Keywords: Dairy cattle; Crude protein; In-vitro gas fermentation assay; Metabolizable energy; Organic matter digestibility